Dislipidemia and systemic inflammation in HIV-infected patients against combined antiretroviral therapy. - V. A. Vasylenko (Medičnì Perspektivi)
There were screened 142 HIV-infected patients receiving combined antiretroviral therapy (сART) for at least 6 months and who reached a level of viral load (HIV-RNA) less than 50 copies/ml and without  clinical manifestations of cardiovascular disease. The study did not include patients with acute inflammation, the number of CD4 + T lymphocytes less than 200 cells/ml, patients with drug addiction and alcoholism. The aim of the study was to establish the severity of dyslipidemia and systemic inflammation in HIV-infected patients, depending on the level of CD4 + T-lymphocytes. It has been established that among patients with HIV receiving сART for a long time, a highly aterogeneic dyslipidemia IIb according to the classification D. Fredrickson develops. Negative prognosis for the course of atherosclerosis in this category of patients is confirmed by a high concentration of С-reactive protein (CRP). An effective сART promotes the reduction of levels of total cholesterol, triglycerides and atherogenicity index against the background of increased high density lipoproteins. At the same time, the concentration of low density lipoproteins does not change and the level of CRP does not decrease sufficiently, which indicates to an unfavorable prognosis for the risk of atherosclerosis progression and cardiovascular complications in HIV-infected patients.